Impact of Artificial Intelligence (AI) on Environmental Security (ES) of Post-Pandemic Covid-19: A Literature Review Study - Alblooshi, Helal; Haryati Shafii, (Research in Management of Technology and Business, 2024)
The rapid advancement of Artificial Intelligence (AI) has brought innovative solutions to diverse industries. The global COVID-19 pandemic serves as a stark reminder of AI's critical role in environmental security (ES). The pandemic induced significant shifts in human activities and global dynamics, unveiling environmental challenges and opportunities. The movement restrictions and economic slowdowns temporarily improved air quality, reduced water pollution, and diminished carbon emissions in numerous cities. The pandemic simultaneously unveiled the inadequacies of existing ES systems in effectively addressing and mitigating environmental threats. AI emerges as a solution for reinforcing ES, particularly as the pandemic disrupted traditional environmental efforts and catalysed innovation in remote work and digital solutions, offering the potential for long-term reductions in carbon footprints. Therefore, this review aims to explore the post-pandemic impact of AI on ES. The study examines various vital areas where AI technologies are applied, encompassing climate modelling, disaster management, biodiversity conservation, and sustainable resource allocation. Additionally, it also delves into ethical considerations and potential risks associated with the expanded use of AI in environmental contexts. This study employs a comprehensive literature review which involves analysing existing research and scholarly articles on AI and ES. Moreover, thematic analysis was utilised to identify recurring themes and patterns in the literature, helping to gain deeper insights into the subject matter.  This analytical approach elucidates the multifaceted relationship between ES in the post-COVID-19 era and AI, emphasising the potential of AI-driven solutions to construct a more sustainable and resilient post-pandemic world while highlighting the importance of ethical considerations in AI deployment. The synthesis of information through thematic analysis enriches our understanding of how AI can stimulate innovation and sustainability, promising a more secure environment in the post-COVID-19 world. In conclusion, this literature review underscores the profound impact of COVID-19 on ES and highlights AI's role in addressing the challenges and opportunities that have emerged in the post-pandemic era.